Preparation of MA students for presenting professional texts in English - Danijela B. Mišić (Inovacije u Nastavi, 2025)
The author of the paper points out the importance of good methodological and linguistic preparation of master students at the faculties of education for presenting professional, popular-science, and literary texts written in English. The goal is to raise the level of fluency in English and enable the future teacher to use it to motivate students and for a better reception of the teaching material. It has been observed that speech in a given dialogical text is realized through the multimedia approach: through words, gestures, mime, sound, and image, all of which have an inevitable psychological, social, aesthetical and cultural function. The theoretically explained preparation, supported by the extract from the novel Alice in Wonderland by Lewis Carroll, showed that a better reception of a literary work can be achieved by putting it on stage as well.